High temperature corrosion-fatigue behavior of a shot peened nickel based superalloy - Yong Li (Corrosion Science, 2022)
As turbine entry temperatures (TET) in modern gas turbine engines continue to increase, Type II hot corrosion has the potential to be a significant damage mechanism at turbine disk rims as temperatures approach 700°C. Therefore, assessment of the effect of hot corrosion damage is essential. In the current research, low cycle corrosion-fatigue behavior of a newly developed polycrystalline nickel superalloy was investigated. The testing programme involved consideration of the variations in fatigue life brought about by changes in surface condition when tested at 700°C in a representative service environment. The high temperature corrosion-fatigue resistance behavior is compared with a previous generation alloy, and detailed fractography to identify the mechanisms of fatigue crack initiation is discussed. High temperature corrosion-fatigue behavior is also correlated to the shot peened work hardened layer.